New Complexity Weights for Function Point Analysis Using Artificial Neural Networks - Mohammed Abdullah, Hasan Al-Hagri (2004)
Function points are intended to measure the amount of functionality in a system as described by a specification. Function points are first proposed in 1979 and currently they are known as the International Function Points User Group (IFPUG) version 4.1. Function points are computed through three steps. The first step is counting the number of the five components in a system which are external inputs, external outputs, external inquiries, external files, and internal files. The second step is assigning a complexity weight to each of the components using weighting factors that are established according to the ordinal scale: simple, average, or complex. The last step is determining 14 technical complexity factors. Although, function points are widely used, they still have limitations.